Assessment of CAR T cell frequencies in axicabtagene ciloleucel and tisagenlecleucel patients using duplex quantitative PCR - Schubert, Maria-Luisa; Kunz, Alexander; Schmitt, Anita; Neuber, Brigitte; Wang, Lei; Hückelhoven-Krauss, Angela; Langner, Sascha; Michels, Birgit; Wick, Antje; Daniel, Volker; Müller-Tidow, Carsten; Dreger, Peter; et al. (Cancers, 2020)
Chimeric antigen receptor (CAR) T cell (CART) therapy has been established as a treatment option for patients with CD19-positive lymphoid malignancies in both the refractory and the relapsed setting. Displaying significant responses in clinical trials, two second-generation CART products directed against CD19, axicabtagene ciloleucel (axi-cel) and tisagenlecleucel (tisa-cel), have been approved and integrated into the clinical routine. However, experimental assay for quantitative monitoring of both of these CART products in treated patients in the open domain are lacking. To address this issue, we established and validated a quantitative single copy gene (SCG)-based duplex (DP)-PCR assay (SCG-DP-PCR) to quantify CARTs based on the FMC63 single chain variable fragment (scFv), i.e., axi-cel and tisa-cel. This quantitative PCR (qPCR) approach operates without standard curves or calibrator samples, offers a tool to assess cellular kinetics of FMC63 CARTs and allows direct comparison of CART-copies in axi-cel versus tisa-cel patient samples. For treating physicians, SCG-DP-PCR is an important tool to monitor CARTs and guide clinical decisions regarding CART effects in respective patients.
Gesehen am 24.11.2020